Media pedagogical competence requirements for teachers in adult education: perspectives of practice - Bolten, Ricarda; Rott, Karin Julia (MediaEducation: Journal for Theory and Practice of Media Education, 2018)
Digitalisation is more and more affecting teaching and learning processes in adult education. As a result, the requirements faced by teachers in adult education are changing. In addition to changes in teaching and learning, the teachers should have media-related competencies in various areas to be able to act competent in a media pedagogical way and thereby meet the requirements of digitisation. Without broad media pedagogical competences, teachers nowadays can hardly comply with all their responsibilities.This paper examines practical perspectives on the requirements of media pedagogical competence of teachers in adult education as orientation points for the design of media pedagogical professionalisation. For this purpose, the results of interviews and focus groups with planning/deciding staff and teachers in adult education are presented. The interweaving of the perspectives of different actors in the field of adult education reveals that in addition to media pedagogical competences of the teachers, also the organisational, external circumstances in adult education influence the media usage.For an up-to-date system of adult and further education, in which teachers use digital media competently and meaningfully, the demands of organisational and institutional levels need to be more transparent to the teachers. These descriptions and a model of media pedagogical competence could give orientation for an individual professionalisation for teachers in adult education.